Udany powrót etosu szlacheckiego na turystyczne szlaki Wielkopolski - Buczkowska, Karolina (Studia Etnologiczne i Antropologiczne, 2014)
The article presents the issue of the fall of the gentry ethos in Poland several years ago and its current return to the tourist trails of Wielkopolska. The author describes services and achievements of some chosen gentry (landowning) families from Wielkopolska Region and their properties, as well as she points out to tourist trails, museums and exhibition rooms and other forms tourism activity (such as quests, theme events and historic reenactments) which were created on their basis.